Penguatan Tata Kelola Perkotaan melalui Standardisasi Alamat: Pendekatan Sistem Informasi Transisi di Indonesia - I Made Andi Darma Kesuma; Heri Sutanta; Wahyu Handoyo; Pamungkas; Arief Amrullah (Research and Development Agency Ministry of Home Affairs, 2026)
Unstructured, narrative-based addressing systems in many developing countries fragment spatial data management and hinder effective urban governance. Although Indonesia has formally established a national standard for urban and rural addressing (SNI 9037:2021), implementation remains limited, resulting in inconsistent, non-geocoded, and non-interoperable address records. Strengthening address standardization is therefore essential to improve public service delivery, spatial data integration, and national data interoperability. This study proposes a web-based address information system designed as a transitional mechanism to support the gradual implementation of standardized addressing without immediately eliminating locally embedded address practices. Using Mantrijeron subdistrict in Yogyakarta City as a case study, we develop a dual-schema geospatial database and a hybrid search mechanism that link existing community-based addresses to standardized formats. The results show that the system maps descriptive local address queries to standardized, spatially referenced building records. The transitional dual-system model allows local governments to promote address standardization while maintaining operational usability during the transition period. A usability evaluation indicates strong user acceptance among initial users, although readiness for broader implementation remains to be established. We conclude that effective address standardization in developing contexts may benefit from adaptive and inclusive digital strategies. Rather than imposing abrupt top-down reforms, transitional information systems can facilitate gradual compliance with national standards while strengthening urban governance and supporting the One Data Indonesia framework.